Contemporary financial intermediation - Greenbaum, Stuart I. (Dryden Press, 1995)
For courses in financial institutions, banking, financial intermediation, MBA Bank Management courses, or Ph.D. intermediation courses, this is the only banking text that is primarily analytical rather than descriptive.